Is takeout culture associated with rising colorectal cancer in young Chinese adults? An ecological analysis of GBD and CHNS data - Yao, Ling; Li, Yufei; Yao, Yuqiao; Qian, Guixiang; Zhang, Zhuhui; Liu, Qiuling; Dai, Jie; Lei, Xuedi; Jia, Xiaoqiang; Quan, Longfang; Li, Haixia; Li, Yonghai (Frontiers in Public Health, 2025)
ObjectiveTo explore the epidemiology of diet-related diseases and shifts in dietary habits among frequent takeout consumers in China over the previous decade.MethodsThis study utilized data from the Global Burden of Disease (GBD) 2021 to analyze incidence trends of 12 diet-related diseases, including nutritional deficiencies, non-neoplastic digestive diseases, and gastrointestinal cancers, spanning from 2010 to 2021. Additionally, we assessed changes in Disability-Adjusted Life Years (DALYs) attributable to various risk factors. Changes in dietary behavior among young Chinese adults were evaluated using data from the China Health and Nutrition Survey (CHNS).ResultsThe standardized incidence of Vitamin A deficiency has consistently declined over the past decade. Among non-neoplastic digestive diseases, inflammatory bowel disease showed the most pronounced decrease. In contrast, the burden of colorectal cancer has increased annually across all age groups. Significant risk factors for colorectal cancer—including low intake of whole grains and milk, and high consumption of red and processed meats, as well as smoking—have contributed to an increase in DALYs in 2021 compared to 2010. Additionally, these shifts in beverage consumption—particularly the steep rise in soft drinks—are a key public health concern given their established dietary risks. Critically, their temporal coincidence with the explosive growth of the takeout market posits the delivery ecosystem as a potential amplifier of these unhealthy dietary patterns.ConclusionFrom 2010 to 2021, colorectal cancer incidence rose among Chinese adults aged 20–39, despite declining burdens of nutritional deficiencies and non-neoplastic digestive diseases. This trend parallels shifts in dietary behavior and the rapid growth of the takeout industry. These findings call for further research into causal links and platform-based public health interventions promoting healthier diets.